Global monetary and financial spillovers: Evidence from a new measure of Bundesbank policy shocks - James S. Cloyne; Patrick Hürtgen; Alan M. Taylor (Deutsche Bundesbank, 2022)
Identifying exogenous variation in monetary policy is crucial for investigating central bank policy transmission. Using newly-collected archival real-time data utilized by the Central Bank Council of the German Bundesbank, we identify unexpected changes in German monetary policy from 580 policy meetings between 1974 and 1998. German monetary policy shocks produce conventional effects on the German domestic economy: activity, prices, and credit decline significantly following a monetary contraction. But given Germany's central role in the European Monetary System (EMS), we can also shed light on debates about the international transmission of monetary policy and the relative importance of the U.S. Federal Reserve for the global cycle during these years. We find that Bundesbank policy spillovers were much stronger in major EMS economies with Deutschmark pegs than in non-EMS economies with floating exchange rates. Furthermore, compared to monetary spillovers from the U.S., German spillovers were comparable or even larger in magnitude for both pegs and floats.
Keywords: E32; E52; F42; F44; 330; Monetary policy; Bundesbank; trilemma; exchange rate; spillovers; Geldpolitik; Geldpolitische Transmission; Wechselkurs; Wechselkurspolitik; Internationaler Finanzmarkt; Europäisches Währungssystem; Deutschland